Logistic chaotic sequence generator based on physical unclonable function - Chunguang HUANG; Hai CHENG; Qun DING (Tongxin xuebao)
Logistic nonlinear chaotic system has many good characters such as initial value sensitivity and topological mixing in the some parameter condition,which is used to create the random sequence signal generator.Because of the attributions of randomness and uniqueness even under the exact,the same circuit layouts and manufacturing procedures,there is still an instinct unclonable difference in each integrated circuit.Therefore,a new sequence stream generator was proposed based on Logistic chaotic system and physical unclonable function designed by double output look-up-table (LUT).The output of the Logistic sequence generator was associated with a specific physical circuit.This kind of sequence generator could resist an attack such as the replication of the keys of the system.The system was designed and tested on the Xilinx FPGA board.The results show that the same architecture of the circuit and the same config file operated on the different FPGA developing board can generate the total different random chaotic sequence stream and improve the randomness of the stream.